2004
DOI: 10.2298/jsc0402153j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical formation and characterization of Ag2O

Abstract: The process of Ag2O formation has been investigated in 0.1M, 0.3 M, 1.0Mand 2.0 M NaOH solutions on polycrystalline Ag electrodes by cyclic voltammetry potentiostatic pulse and SEM techniques. The SEM micrographs of the chemically polished Ag surface and the surface after oxide formation revealed considerable roughening of the Ag surface after Ag2O formation and reduction. The roughening was more pronounced at higher NaOH concentrations, indicating that only the first cycle or pulse applied on a freshly polish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 12 publications
4
50
0
8
Order By: Relevance
“…Becerra et al [41] have reported that the secondary silver (I) oxide layer can be formed on the primary silver(I) oxide layer by the instantaneous nucleation and 3D growth mechanism under diffusion control. SEM micrographs confirm that the two anodic peaks present on the voltammograms of Ag 2 O formation correspond to two types of oxide film, i.e., nonhomogeneously and homogeneously distributed types [28,29] So, the peaks A 4 and A 5 on our voltammograms are to be connected to formation of these two types of silver(I) oxide, whereas Reaction [7] can be attributed to the peak A 6 .…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Becerra et al [41] have reported that the secondary silver (I) oxide layer can be formed on the primary silver(I) oxide layer by the instantaneous nucleation and 3D growth mechanism under diffusion control. SEM micrographs confirm that the two anodic peaks present on the voltammograms of Ag 2 O formation correspond to two types of oxide film, i.e., nonhomogeneously and homogeneously distributed types [28,29] So, the peaks A 4 and A 5 on our voltammograms are to be connected to formation of these two types of silver(I) oxide, whereas Reaction [7] can be attributed to the peak A 6 .…”
Section: Resultssupporting
confidence: 68%
“…To recognize these reactions, the voltammogram obtained on sintered alloy is compared with the voltammograms obtained on pure copper and silver ( Figure 5). The current peak A 1 is attributed to the adsorption of OH − and formation of the first oxide monolayer based on literal [10][11][12][13][14][15][16][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] data to which, with different in situ techniques, the presence of absorbed hydroxyl ions on the surface of copper and silver in alkaline electrolytes is proved in the quoted area of potential. It is obvious that the current waves marked as A 2 and A 3 correspond to copper oxides formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 mV and a corresponding reduction peak (C) seen at potentials more negative than 100 mV (the exact location depends on the amount of Ag compounds subjected to the reduction [37,69]). Detailed discussion of the processes related to the anodic currents (A) can be found elsewhere [21][22][23][24][25][26][27][28][29][70][71][72][73][74][75]. Various products of Ag oxidation at potentials up to ca.…”
Section: Resultsmentioning
confidence: 99%
“…Silver oxidation in an alkaline electrolyte starts at ca. 10 mV vs. Hg|HgO; the usually reported oxidation products are Ag 2 O and AgO, depending on the oxidation potential [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. AgO is described as a mixture of Ag(I) and Ag(III) species [11,39,40].…”
Section: Introductionmentioning
confidence: 99%